Inovasi Pertanian Berkelanjutan di Era Digital - Muhammad Khalish; Muhammad Azizi; Ayu Naziha; Putri Asyifa; Cut Putri Erika; Novia Yunanda (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The development of digital technology has brought significant changes to the agricultural sector, particularly in supporting the implementation of sustainable agriculture. Digital innovations such as the Internet of Things (IoT), precision agriculture, and agricultural information systems play an important role in improving production efficiency while preserving environmental sustainability. This study aims to examine the role of sustainable agricultural innovations in the digital era in enhancing productivity and sustainability in the agricultural sector. The method employed is a literature review by analyzing various relevant scientific publications. The results indicate that the utilization of digital technology can improve the effectiveness of resource management and assist farmers in making more accurate and informed decisions.